2007
DOI: 10.1134/s0006297907100112
|View full text |Cite
|
Sign up to set email alerts
|

“Blue” laccases

Abstract: This review concerns copper-containing oxidases--laccases. Principal biochemical and electrochemical properties of laccases isolated from different sources are described, as well as their structure and mechanism of catalysis. Possible applications of laccases in different fields of biotechnology are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
307
0
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 386 publications
(331 citation statements)
references
References 185 publications
14
307
0
10
Order By: Relevance
“…These results are in agreement with previous reports where the maximal bioelectrocatalytic activity of Lc from different sources was observed in the temperature range 35 -50°C [41][42][43][44]. While the solubility of O 2 decreases with increasing temperature, the increase in the diffusion coefficient offsets this decrease, resulting in an increased response [37,[45][46] which is in agreement with the results reported for homogeneous ThLc catalysis which has a temperature optimum of 45°C [47]. A small peak was observed at 0.7 V. The origin of the peak is unclear, it is not related to temperature effects at 45 o C as it has been observed previously at room temperature [22,35].…”
Section: Resultssupporting
confidence: 93%
“…These results are in agreement with previous reports where the maximal bioelectrocatalytic activity of Lc from different sources was observed in the temperature range 35 -50°C [41][42][43][44]. While the solubility of O 2 decreases with increasing temperature, the increase in the diffusion coefficient offsets this decrease, resulting in an increased response [37,[45][46] which is in agreement with the results reported for homogeneous ThLc catalysis which has a temperature optimum of 45°C [47]. A small peak was observed at 0.7 V. The origin of the peak is unclear, it is not related to temperature effects at 45 o C as it has been observed previously at room temperature [22,35].…”
Section: Resultssupporting
confidence: 93%
“…Laccases are oxidoreductases or multi-copper oxidases that are widely used to oxidize a variety of dye by-products by coupling reduction of oxygen to water with concomitant oxidation of the dye product substrates (Kurniawati & Nicell, 2007Morozova et al, 2007). Laccases catalyze decolorization of textile dyes either by direct oxidation or via indirect oxidation using mediators to accelerate the Detoxification of azo dyes by bacteria 7…”
Section: Oxidative Enzymesmentioning
confidence: 99%
“…In order to determine the molecular structure of the synthesized product and to assign all the 1 H and 13 C signals, 1 H-13 C HSQC and 1 H- 13 C HMBC experiments were performed (results now shown). All these findings suggested that they belong to a six carbon quinone-ring.…”
Section: Amount Of Laccase (U)mentioning
confidence: 99%
“…Laccase is a copper-containing oxidase that catalyzes reduction of molecular oxygen to water and the oxidation of a phenolic compound 13 . Also, dimerization, oligomerization, and polymerization of phenolic compounds can be obtained 8 .…”
Section: Introductionmentioning
confidence: 99%